Gender and Relatability in Digital Culture Managing Affect, Intimacy and Value - Kanai, Akane (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book explores the practices and the politics of relatable femininity in intimate digital social spaces. Examining a GIF-based digital culture on Tumblr, the author considers how young women produce relatability through humorous, generalisable representations of embarrassment, frustration, and resilience in everyday situations. Relatability is examined as an affective relation that offers the feeling of sameness and female friendship amongst young women. However, this relation is based on young women's ability to competently negotiate the 'feeling rules' that govern youthful femininity. Such classed and racialised feeling rules require young women to perfect the performance of normalcy: they must mix self-deprecation with positivity; they must be relatably flawed but not actual 'failures'. Situated in debates about postfeminism, self-representation and digital identity, this book connects understandings of digital visual culture to gender, race, and class, and neoliberal imperatives to perform the 'right feelings'. Gender and Relatability in Digital Culture will be of interest to students and scholars across a range of disciplines including gender studies, cultural studies, sociology, and media studies.